(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
Modeling aims to characterize system behavior and achieve simulation close as possible of the reality. The rapid energy exchange in supercritical flow to generate quiet or subcritical flow in hydraulic jump phenomenon is important in design of hydraulic structures. Experimental and numerical modeling is done on type B hydraulic jump which starts first on sloping bed and its end on horizontal bed. Four different apron slopes are used, for each one of these slopes the jump is generated on different locations by controlling the tail water depth. Modelling validation is based on 120 experimental runs which they show that there is reliability. The air volume fraction which creates in through hydraulic jump varied between 0.18 and 0.28. While the energy exchanges process take place within 6.6, 6.1, 5.8, 5.5 of the average relative jump height for apron slopes of 0.18, 0.14, 0.10, 0.07 respectively. Within the limitations of this study, mathematical prediction model for relative hydraulic jump height is suggested.The model having an acceptable coefficient of determination.